The importance of Antarctic krill in biogeochemical cycles - Cavan, EL; Belcher, A; Hill, SL; Kawaguchi, S; McCormack, S; Meyer, B; Nicol, S; Schmidt, K; Steinberg, Deborah K.; Tarling, GA; Boyd, PW (Nature Communications, 2019)
Antarctic krill (Euphausia superba) are swarming, oceanic crustaceans, up to two inches long, and best known as prey for whales and penguins – but they have another important role. With their large size, high biomass and daily vertical migrations they transport and transform essential nutrients, stimulate primary productivity and influence the carbon sink. Antarctic krill are also fished by the Southern Ocean’s largest fishery. Yet how krill fishing impacts nutrient fertilisation and the carbon sink in the Southern Ocean is poorly understood. Our synthesis shows fishery management should consider the influential biogeochemical role of both adult and larval Antarctic krill.